2014
DOI: 10.1016/j.leukres.2014.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and safety of different azacitidine dosage regimens in patients with myelodysplastic syndromes or acute myeloid leukemia

Abstract: We investigated the effectiveness and tolerability of azacitidine in patients with World Health Organization-defined myelodysplastic syndromes, or acute myeloid leukemia with 20-30% bone marrow blasts. Patients were treated with azacitidine, with one of three dosage regimens: for 5 days (AZA 5); 7 days including a 2-day break (AZA 5-2-2); or 7 days (AZA 7); all 28-day cycles. Overall response rates were 39.4%, 67.9%, and 51.3%, respectively, and median overall survival (OS) durations were 13.2, 19.1, and 14.9 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 18 publications
4
38
0
Order By: Relevance
“…27,3739 For example, a report from the Spanish Compassionate use registry of 200 azacitidine-treated patients with all IPSS risk groups estimated an overall median OS of 16.5 months (95% CI, 12.4 – 19.1 months). 38 A report from the Dutch compassionate patient-named program of 90 azacitidine-treated patients estimated a median OS of 13 months. 39 The Groupe Francophone des Myelodysplasies reported a median OS of 13.5 months for 282 patients with HR-MDS treated with azacitidine in the French compassionate, patient-named program.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…27,3739 For example, a report from the Spanish Compassionate use registry of 200 azacitidine-treated patients with all IPSS risk groups estimated an overall median OS of 16.5 months (95% CI, 12.4 – 19.1 months). 38 A report from the Dutch compassionate patient-named program of 90 azacitidine-treated patients estimated a median OS of 13 months. 39 The Groupe Francophone des Myelodysplasies reported a median OS of 13.5 months for 282 patients with HR-MDS treated with azacitidine in the French compassionate, patient-named program.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the details of routes and doses of azanucleoside therapy were not collected, though previous studies have shown little difference in response rates with variation in these parameters. 20,38,45 Compared with this analysis, other studies have calculated survival from date of initiation of the azanucleoside rather than from date of diagnosis. However, since this analysis was limited to patients who presented with HR-MDS, most of whom were symptomatic and were started on azanucleoside therapy soon after diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the AVIDA registry study in the United States indicated that only 15% of patients with MDS who receive azacitidine use the consecutive 7-day administration schedule used in AZA-001, which to our knowledge is the only schedule that has been associated with an OS advantage. 22 It is interesting to note that, in contrast to these observations with azacitidine, the OS observed in real-life and registry analyses of patients with HR-MDS treated with decitabine does not appear to differ substantially from the OS observed in the large 2 randomized clinical trials. 20 Similarly, in the Spanish MDS Registry study, there were no differences in survival noted between in the standard 7-day schedule of azacitidine and less intensive regimens.…”
Section: Many Patients Treated With Hma Monotherapy Do Not Derive Anymentioning
confidence: 89%
“…15 Patients with HR-MDS usually are referred to tertiary centers early in the disease course only if alloHSCT is considered or after HMA failure; the rare younger patient with MDS and those with unusual presentations such as MDS/myeloproliferative neoplasm overlapping syndromes also are more likely to be referred. [8][9][10][11][18][19][20][21][22][23][24][25][26][27] For example, investigators in the MDS Clinical Research Consortium recently described the outcomes of patients in what to our knowledge is the largest reported cohort of patients with HR-MDS treated with HMAs in the United States. 16 Lenalidomide also is often attempted before specialty center referral, despite the limited efficacy of lenalidomide in the non-del5q setting and almost complete absence of activity in patients with HR-MDS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation